2013
DOI: 10.3892/ijmm.2013.1381
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miRNAs in the nervous system of a rat model of bilateral sciatic nerve chronic constriction injury

Abstract: Abstract. Chronic neuropathic pain is associated with global changes in gene expression in different areas of the nociceptive pathway. MicroRNAs (miRNAs) are small (~22 nt long) noncoding RNAs, which are able to regulate hundreds of different genes post-transcriptionally. The aim of this study was to determine the miRNA expression patterns in the different regions of the pain transmission pathway using a rat model of human neuropathic pain induced by bilateral sciatic nerve chronic constriction injury (bCCI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
(47 reference statements)
1
30
0
Order By: Relevance
“…[13] reported spinal miR-146a and -183 cluster expression in osteoarthritic pain of knee joints. Besides, other studies reported the differential expressions of miRNAs in animal models with chronic neuropathic pain induced by lumbar nerve injury at peripheral and central nerve system level [10], [12], [15]. However, there were limited studies reported in the orofacial region.…”
Section: Introductionmentioning
confidence: 99%
“…[13] reported spinal miR-146a and -183 cluster expression in osteoarthritic pain of knee joints. Besides, other studies reported the differential expressions of miRNAs in animal models with chronic neuropathic pain induced by lumbar nerve injury at peripheral and central nerve system level [10], [12], [15]. However, there were limited studies reported in the orofacial region.…”
Section: Introductionmentioning
confidence: 99%
“…90 In the neuropathic pain models, a downregulation of miR-181a or other members of the miR-181 family, namely miR-181b/c/d has been documented. 91,92 In this context, deregulation of miR-181a expression in various brain regions has been reported following chronic exposure to drug of abuse.…”
Section: Activity-dependent Regulation Of M Icrornas In Pain Processingmentioning
confidence: 99%
“…An up regulation of miR-341 in the DRG and down regulation of miR-203, miR-181a-1 and miR-541 in the spinal dorsal horn leads to development of neuropathic pain [29]. Continually, a sciatic nerve ligation (SNL) study shows a drastic decrease in miR200b and miR429 in NAcc neurons [67].…”
Section: Mirnas Therapy For Treating Neuropathic Painmentioning
confidence: 99%
“…In animal models, the dorsal root ganglia, the spinal dorsal horn, and the brain are all areas of miRNA modulation [28]. Following injury, the differential expression of miRNAs in the nervous system may play a role in predicting the development of chronic pain [29]. CED has not been explored extensively as a delivery method for miRNAs in the treatment of NP, recent studies have identified several microRNAs including miR-21, miR-486, miR-20 involved in key mechanisms of SCI such as cell death or astrogliosis, direct evidence on the role of miRNAs in SCI is scarce [30].…”
Section: Additionally There Is a Need To Visualize Target And Contrmentioning
confidence: 99%
See 1 more Smart Citation